The Governance of School Operational Assistance (SOA) Funds for Elementary Schools in Medan - Harmen, Hilma; Dalimunthe, Muhammad Bukhori; Dewi, Rosmala; Panggabean, Fitri Yani; Dalimunthe, Raudah Zaimah (Jurnal Ilmiah Peuradeun, 2023)
This study aimed to test the measurement and structural models of SOA fund governance constructed by participation, transparency, and accountability. A total of 348 respondents were involved in this study consisting, including the headmaster (n=20), teachers (n=76), and parents (n=252). Data were collected using a questionnaire distributed to respondents using Google Forms for four months. Data analysis used confirmatory factor analysis through Partial Least Squares-Path Modeling (PLS-PM), which assisted the Smart PLS. Testing the measurement model using construct validity and internal consistency reliability showed two items (P4-participation and A3-accountability) having loading factors that do not satisfy the criteria. Likewise, both items were excluded from the model, which impacted the acceptance of the model fit. Furthermore, testing the quality of the structural model using the goodness of fit (GoF=0.524) was more significant than 0.36, which meant the quality of the structural model was very strong and significant. The transparency aspect had the most robust coefficient, which signals that everyone regarding the implementation of SOA funds in schools freely obtained the disclosure of financial and academic information. Other scholars can explore the role of the principal, teachers, and parents in making learning successful in schools by optimizing the use of SOA funds.